REMOVAL OF DDD AND DDE FROM WASTEWATER USING BAGASSE FLY ASH, A SUGAR INDUSTRY WASTE - Gupta V.K.; Ali I. (My University, 2001)
Bagasse fly ash, a waste from the sugar industry, was converted into an effective adsorbent and was used for the removal of DDD [2,2-Bis(4-chlorophenyl)-1,1-dichloroethane] and DDE [2,2-Bis(4-chlorophenyl)-1,1-dichloroethene] pesticides from wastewater. The DDD and DDE are removed by the developed adsorbent up to 93% at pH7.0, with the adsorbent dose of 5g/l of particle size 200-250μm at 30°C. The removal of these two pesticides was achieved up to 97-98% in column experiments at a flow rate of 0.5ml/min. The adsorption was found to be exothermic in nature. The bagasse fly ash system has been used for the removal of DDD and DDE from the wastewater. The developed system is very useful, economic, and reproducible.
Keywords: ADSORPTION; BAGASSE FLY ASH; DDD; DDE